Passive Q-switching of an Yb:GdCa4O(BO3)3 laser induced by a few-layer Bi2Te3 topological insulator saturable absorber. (23rd October 2018) - Yang, Jingnan; Li, Yuhang; Tian, Kan; Liu, Fenfen; Dou, Xiaodan; Ma, Yanjun; Han, Wenjuan; Xu, Honghao; Liu, Junhai
Abstract: We report on efficient passively Q-switched operation of an Yb:GdCa4 O(BO3 )3 laser induced by a few-layer Bi2 Te3 topological insulator saturable absorber. A maximum average output power of 2.38 W is produced at a repetition rate of 325 kHz with a slope efficiency of 36%; the resulting pulse energy, duration, and peak power are respectively 7.32 µ J, 104 ns, and 70.4 W. The results obtained in our work demonstrate the potential of Yb:GdCa4 O(BO3 )3 crystal in the development of passively Q-switched solid-state lasers using 2D topological insulator saturable absorbers.